PENGARUH PROMOSI, KUALITAS PELAYANAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA SHOPEE - Marco Manggora Jeremy Napitupulu; Jenji Gunaedi Argo (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This study is a quantitative study and aims to determine the influence of promotion, service quality, and their image on the purchasing decisions of Shoppe users in the DKI Jakarta area. The population in this study are Shopee application users in the DKI Jakarta area with the criteria of having made a purchase more than twice in the last six months. Sampling using non-probability sampling method with purposive sampling technique, with a total sample of 100 respondents. The data analysis technique was carried out by descriptive and inferential analysis with Partial Least Square (PLS) stone tools. The results of this study indicate that the promotion variable has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, and brand image has a positive and significant effect on purchasing decisions. The results of the calculation of the coefficient of determination are 0.729. This shows that promotion, service quality, and brand image affect thepurchasing decisions of Shopee users by 72.9% and the remaining 26.1% is influenced by other variables such as price, product quality and others. Keywordsi: Purchase Decision; Promotion; Service Quality; Brand Image